IMMOBILISATION OF ASPERGILLUS FLAVUS STRAIN S4 SPORES FOR OPTIMAL PRODUCTION AND ACTIVITY OF L-GLUTAMINASE - Lakshmi B.K.M1, a, Chandana Vineela K2, b, Sowjanya M3, c, Hemalatha V4, d*, G Vidya Sagar Reddy5, e, Kalyani P6, f (Chelonian Research Foundation, 2023)
The ever-increasing applications of enzymes are limited by the relatively poor performance in harsh processing conditions. As a result, there are constant innovations in immobilization protocols for improving biocatalyst activity and stability. Bacterial spores are cheap to generate and highly resistant to environmental stress. The results of the present study showed that calcium alginate is a promising method for the immobilization of spores of A. flavus strain S4. L-glutaminase production was maximum at 72 h of incubation. In case of free spores, 48 h of incubation was sufficient for maximum L-glutaminase production. L-glutaminase production was increased even though incubation time was prolonged. Enzyme immobilization study revealed that there was a change in kinetic parameters with marginal increase in enzyme activity at 40oC, pH- 7.0, incubation period- 72 h, inoculum size- 2%, carbon source- dextrose and nitrogen source- combination of ammonium nitrate and yeast extract. Key Words: L-Glutaminase, Immobilization, Aspergillus flavus